Handshake, No. 16 (June 2015) : A Public-Private Partnerships Journal - World Bank Group (Washington, DC, 2016)
The latest issue of Handshake, focused on public-private partnerships in the Innovation. “An age of constant invention naturally begets one of constant failure,”the New York Times Magazine declared in a recent story called “Welcometo the Failure Age.” Its core premise—that innovation is inextricably linked with failure—may be a fresh insight for the high-tech era, but has long been understood by those who work in infrastructure. To state the obvious:for those of us in infrastructure PPPs, failure is not a novel concept.Innovation is. The interplay between the two, with attention to the iterativelearning that is necessary to morph missteps into course corrections. Once the seeds of those ideas are planted, innovation has already begun to germinate. This issue includes the following headings: inside Korea’s PPP unit reinvigorating the regional economy; innovating at scale less early adoption,more global adaptation; The politics of PPP barcelona partnership energizes urban center; redefining failure and success why the “Brilliant Mistake” matters; course corrections small changes that create better outcomes; reviving the reliance rail PPP turning around a difficult project; protecting your PPP stabilizing partnerships in uncertain times; PPP insider Korea’s PPP unit creates institutional memory; from lessons to principles The public governance of PPPs; money talks debunking the myth of the “quick and easy” PPP; inside infrastructure powering rural Africa; One question eight experts discuss how PPPscan absorb common mistakes; master class preventing renegotiation, fostering efficiency; What the rest of the world is saying about PPPs.